Learning Model of Islamic Religious Education and Character During the Pandemic Period at SMP Negeri 8 Purwokerto - M Makhful (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
The sudden onset of the Covid-19 pandemic has an impact on all aspects of life. In the aspect of education, it is needed how to do it with existing resources, existing technology, education can continue to run well, be conducive and the learning process can be conveyed properly. So that learning can continue, collaboration is maintained, then all elements are responsible for education. Learning Islamic religious education and character will be successful if there is an appropriate model that can be practiced during the pandemic, so that learning continues and can meet expectations. This research aims to identify and analyze the learning model of Islamic religious education and manners during the pandemic at SMP Negeri 8 Purwokerto. This research is a qualitative descriptive study with the subject of research being Islamic religious education teachers and character at SMP Negeri 8 Purwokerto. Data collection techniques through observation, interviews and documentation, while data analysis with data reduction, data presentation and drawing conclusions. The results showed that the learning model of Islamic Religious Education and Morals at SMP Negeri 8 Purwokerto used; a) Contextual Teaching and Learning is a learning strategy that emphasizes the process of full student involvement to find the material being studied and relate it to real-life situations and apply it in life. b) Direct Learning, learning that emphasizes mastery of concepts and or behavior change by prioritizing a deductive approach. c) Project Based Learning, a learning method that uses projects or activities as media. Evaluation is carried out through 3 types, namely; a) Assessment of observations / journals on student attitudes, carried out continuously through teacher observations. b) Self-assessment, an assessment carried out by asking students to express their strengths and weaknesses in behavior. c) Assessment between friends, carried out by means of students assessing each other's behavior.